Relationship between Management Control and Lean Management: A systematic literature review - LAMSARNI , Zineb; RANNANE , M’hamed (Revue Internationale du Chercheur, 2025)
Abstract : In an environment characterized by market instability, rapid technological advancement, and intensified competition, companies must optimize performance while preserving agility and adaptability. This requirement reveals structural tensions between two managerial logics: management control, focused on planning and control, and Lean management, oriented toward flexibility, customer value, and continuous improvement. In this context, the articulation between Lean management and management control has gained increasing interest in both academic research and managerial practice. This article aims to conduct a systematic literature review on the nature of this relationship. It seeks to analyze the evolution of knowledge and to highlight the mechanisms and drivers influencing this articulation. A corpus of 50 articles, identified through keyword searches in three academic databases, forms the foundation of this analysis. The study explores the conceptual foundations of this relationship, the dominant theoretical frameworks, and the key assumptions on which researchers base their work. The objective is to identify the main contributions of the literature, reveal current gaps, and propose directions for future research.